Analysis of the expression levels and diagnostic value of serum tumor necrosis factor-like weak inducer of apoptosis and vasohibin-1 in children with purpura nephritis - Hou Xiao-feng; Chen Bin (Linchuang shenzangbing zazhi)
ObjectiveTo detect the serum levels of tumor necrosis factor-like weak inducer of apoptosis （TWEAK） and vasohibin-1 （VASH-1） in children with Henoch-Schönlein purpura nephritis （HSPN）， and to analyze their diagnostic value.MethodsA total of 106 children with confirmed HSPN admitted to Laizhou City People's Hospital from August 2018 to August 2022 were regarded as the HSPN group， and 106 children with Henoch-Schönlein purpura （HSP） were regarded as the HSP group. During the same period，106 healthy children who underwent physical examination in our hospital were included in the control group. Enzyme linked immunosorbent assay （ELISA） was applied to detect serum TWEAK and VASH-1. Pearson method was applied to analyze the correlation between serum TWEAK and VASH-1 expressions in children with HSPN. Receiver operating characteristic （ROC） curve was plotted to analyze the diagnostic value of TWEAK and VASH-1 for HSPN. Multivariate Logistic regression was applied to analyze the risk factors for HSPN.ResultsSerum TWEAK and VASH-1 levels in the HSPN group were 61.82 ± 17.94 ng/L and 342.19 ± 54.37 ng/L， respectively， which were significantly higher than those in the HSP group［TWEAK：（41.89 ± 12.26）ng/L、VASH-1：（288.76 ± 41.68）ng/L］ and the control group［TWEAK：（35.94 ± 10.18）ng/L、VASH-1：（275.46 ± 35.81）ng/L］. Serum TWEAK and VASH-1 were significantly higher in the HSP group than the control group （all P<0.001）. Compared with the low expression groups of TWEAK and VASH-1， patients in the high expression groups of TWEAK and VASH-1 had significantly higher renal pathological grade， 24 h urinary protein， Cystatin C （Cys C）， serum creatinine （Scr）， urinary albumin （Alb）， blood urea nitrogen （BUN）， and urinary immunoglobulin A （IgA） （P<0.05）. Serum TWEAK was positively correlated with serum VASH-1 in children with HSPN （r=0.657， P<0.001）. The area under the curve （AUC） of TWEAK combined withVASH-1 in the diagnosis of HSPN was 0.939 （95%CI：0.898-0.967）， with the sensitivity of 84.91%， and the specificity of 88.68%. TWEAK （OR=1.528， 95%CI：1.145-2.038）， VASH-1 （OR=1.612， 95%CI：1.081-2.404）， 24-hour urine protein （OR=1.652， 95%CI：1.044-2.613）， Cys C （OR=1.498， 95%CI：1.090-2.058）， Scr （OR=1.715， 95%CI：1.061-2.772）， and IgA （OR=1.395，95%CI：1.107-1.758） were all risk factors for the occurrence of HSPN （P<0.05）.ConclusionsTWEAK and VASH-1 are highly expressed in the serum of children with HSPN， and they are closely related to renal function damage indicators in HSPN. They are both risk factors for HSPN and have certain diagnostic value for HSPN.